2009
DOI: 10.1097/mcg.0b013e318167b8cc
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound Versus CT Scan for Detection of the Metastases to the Liver

Abstract: In comparison with the CT scan, there was trend in favor of EUS/EUS-FNA for the superior diagnostic accuracy. EUS was distinctly superior to the CT scan in detecting the number of metastatic lesions. EUS-FNA was also useful to identify the nature of lesions that were too small to be characterized on the CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 10 publications
1
62
0
1
Order By: Relevance
“…1,2 EUS FNA of the liver has been used to evaluate specific liver lesions and these have included both primary and metastatic malignancies. [3][4][5][6][7][8][9] It has been shown to be safe, efficacious, and diagnostic. 10 This study identified 102 cases where both the pancreas and liver were biopsied concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 EUS FNA of the liver has been used to evaluate specific liver lesions and these have included both primary and metastatic malignancies. [3][4][5][6][7][8][9] It has been shown to be safe, efficacious, and diagnostic. 10 This study identified 102 cases where both the pancreas and liver were biopsied concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that EUS can identify small metastatic lesions that were not identified on CT, including left lobe liver metastases, perivascular cuffing by tumor, and malignant involvement of celiac ganglia. [18][19][20] The ability to obtain tissue specimens from these sites or from the primary pancreatic mass is increasingly important. Pancreatic mass lesions may be adenocarcinoma, other neoplasms such as neuroendocrine tumors or metastases, or benign conditions such as autoimmune pancreatitis, and these lesions cannot always be differentiated by clinical findings, imaging, and laboratory tests.…”
Section: Tumor Stagingmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Moreover, EUS-guided FNA of both regional and distant lymph nodes adds to the accuracy of nodal staging. 15,16 The role of EUS in gastric cancer can be categorized as follows:…”
Section: Role Of Eusmentioning
confidence: 99%